Isometric shoulder strength in young swimmers - McLaine, S. J.; Ginn, K. A.; Fell, J. W.; Bird, M.-L. (Journal of Science and Medicine in Sport, 2018)
Objectives: The prevalence of shoulder pain in young swimmers is high. Shoulder rotation strength and the ratio of internal to external rotation strength have been reported as potential modifiable risk factors associated with shoulder pain. However, relative strength measures in elevated positions, which include flexion and extension, have not been established for the young swimmer. The aim of this study was to establish clinically useful, normative shoulder strength measures and ratios for swimmers (14-20 years) without shoulder pain. Design: Cross-sectional, observational study. Methods: Swimmers (N = 85) without a recent history of shoulder pain underwent strength testing of shoulder flexion and extension (in 140° abduction); and internal and external rotation (in 90° abduction). Strength tests were performed in supine using a hand-held dynamometer and values normalised to body weight. Descriptive statistics were calculated for strength and strength ratios (flexion:extension and internal:external rotation). Differences between groups (based on gender, history of pain, test and arm dominance) were explored using independent and paired t tests. Results: Normative shoulder strength values and ratios were established for young swimmers. There was a significant difference (p < 0.002) in relative strength between males and females for all tests with no differences in strength ratios. Relative strength of the dominant and non-dominant shoulders (except for extension); and for swimmers with and without a history of shoulder pain was not significantly different. Conclusions: A normal shoulder strength profile for the young swimmer has been established which provides a valuable reference for the clinician assessing shoulder strength in this population.